Report on the impact of dynamic capabilities on sustainable competitive advantage in the pharmaceutical sector in Bangladesh - Kadir, Md. Shahariar (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.